Role of superoxide dismutase in modification of radiation injury. - Petkau, A. (Nature Publishing Group, 1987)
The effects of superoxide dismutase on radiobiological end-points are discussed in terms of the time scale of primary radiation chemical reactions and later cellular and physiological processes. The effectiveness of SOD on responsive subpopulations of bone marrow progenitor cells is shown to be temperature- and dose-dependent. Under certain conditions, the protective actions of superoxide dismutase and catalase complement each other in a sequential fashion. Finally, cellular levels of endogenous superoxide dismutase in atomic radiation workers are compared with those in a control population.